Effect of pretreatment of synthetic and natural carbons as starting materials for carbon nanotubes - Ahmad Fauzi Ismail, 1966-; Nor Aziah Buang; Madzlan Aziz; Suhaila Mohd. Sanip; Tee, Jia Chee; International Conference on Materials for Advanced Technologies (2003 : Singapore) (Skudai : Universiti Teknologi Malaysia, 2003)
09